Frequency of Hypocalcemia in Infants of Diabetic Mothers within 24 Hours of Life - Nagham Nawaz Awan, Sumbal Abbas, Marina Naz, Madiha Jameel, Sabika Iftikhar, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To find frequency of Hypocalcemia in infants of diabetic mothers within 24 hours of life. Study Design: It was a cross-sectional study. Study Duration: The study was conducted at paediatric department of Ittifaq hospital Lahore from April 12, 2018 till Oct 12, 2019. Material and Methods: A total of 260 cases after getting approval of synopsis were taken from Neonatal ward after delivery from Ittifaq hospital Lahore. All neonates fulfilling / meeting inclusion criteria were assessed for hypocalcaemia. Their basic history like age (hours), gender, gestational age, birth weight and baseline calcium level were noted. Venous blood was taken for analysis of calcium level and hypocalcaemia was labeled as per operational definition. Results: The mean age of infants was 11.92 ± 6.66 hours with minimum and maximum age as 1 and 24 hours. There were 137(52.7%) male and 123(47.3%) female cases, with higher male to female ratio. The mean gestational age was 39.48 ± 1.68 weeks with minimum and maximum gestational age as 37 and 42 weeks. The mean birth weight was 3193.99 ± 404.12 g with minimum and maximum birth weight as 2500 and 3892 grams. A total of 67(25.8%) neonates had hypocalcaemia while 193(74.2%) neonates had normal calcium level. Practical implication: This study was done to determine the frequency of neonatal hypocalcemia among infants with maternal hypocalcemia due to the lack of data, especially at the local level. If diagnosed early, they can begin treatment right away, which could reduce their mortality and morbidity in our region of the world. Conclusion: Through the findings of this study, it is concluded that, almost a quarter i.e. 25.8% neonates had hypocalcaemia that is considerably high percentage. So, infants born to diabetic mothers should be screened for hypocalcaemia to minimize the risk of related complications like seizure and loss of consciousness etc. Keywords: Pregnancy, diabetes mellitus, gestational diabetes mellitus, calcium level, hypocalcaemia